Evaluasi Implementasi Program MBKM Kampus Mengajar Berbasis CIPP di SDN 010 Melayu Besar - Wardhani, Alfida; Rino, Rino (Jurnal Salingka Nagari, 2024)
This study aims to evaluate the CIPP-based Teaching Campus MBKM program at SDN 010 Melayu Besar. This type of research is an evaluative study with a descriptive approach. The sample in this study was taken based on the key informants, namely the principal and all 7 teachers as well as the Teaching Campus students at SDN 010 Melayu Besar and the sampling technique used was purposive sampling. Data obtained using observation techniques, interviews, questionnaires and documentation. The data obtained is processed with descriptive evaluative. The results showed that the implemented program was the numeracy literacy learning component with an average of 3.95, the teaching component and helping educators with an average result of 4 and the technology adaptation component with an average of 3.29 which means that the implementation of the Teaching Campus program at SDN 010 Melayu Besar as a whole is running very well.